2017
DOI: 10.1016/j.jmmm.2016.12.130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of intrinsic defect magnetic properties in wurtzite ZnO materials

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Hwang et al [29] and Fedorov et al [5], associate the green emission band to undoped ZnO with the presence of VO and VZn [27], [30] that introduces deep acceptors in the Eg. Green luminescence is because of the electronic transition between shallow donors and deep acceptors.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hwang et al [29] and Fedorov et al [5], associate the green emission band to undoped ZnO with the presence of VO and VZn [27], [30] that introduces deep acceptors in the Eg. Green luminescence is because of the electronic transition between shallow donors and deep acceptors.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
“…It is a semiconductor with an n-type conductivity at room temperature [1]. This is mainly attributed to a large number of defects as oxygen vacancies (VO) [2], zinc vacancies (VZn) [3], zinc interstitials (Zni) [4], and oxygen interstitials (Oi) [5]. Several authors have reported a p-type conductivity obtained, only in laboratories,…”
mentioning
confidence: 99%
“…However, when considering the common use of ZnO as an ETL in perovskite solar cells, there still some limitations. Most notably, two major drawbacks stand out: (1) poor perovskite chemical stability on ZnO substrates; and (2) the ZnO/perovskite large interfacial charge recombination due to defects at the wurtzite surface, the most stable phase at ambient temperature [ 25 ]. The ZnO–perovskite interface instability has been widely reported, with a variety of degradation mechanisms proposed [ 4 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of numerous implantation studies often contradict each other because of a lack of agreement on the origin of created magnetic units. It is frequently concluded that the implantation defects rather than the transition metal (TM) impurities give rise to the observed magnetization [1,2]. It was suggested that ferromagnetic (FM) or paramagnetic (PM) phase, observed in ZnO, is either entirely defect related or appearing due to an interaction between defects and implantationintroduced impurities, including those without magnetic moments [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently concluded that the implantation defects rather than the transition metal (TM) impurities give rise to the observed magnetization [1,2]. It was suggested that ferromagnetic (FM) or paramagnetic (PM) phase, observed in ZnO, is either entirely defect related or appearing due to an interaction between defects and implantationintroduced impurities, including those without magnetic moments [2][3][4][5][6]. Since there are reports which attribute magnetic properties to the irradiation created defects like V Zn [2], in our previous publication [7] we attempted to disclose PM/FM phase in ZnO samples containing no TM impurity but only defects.…”
Section: Introductionmentioning
confidence: 99%